STUDIES ON THE BEHAVIOR OF THE SINTERED MATERIAL BASED ON IRON POWDER TO MECHANICAL COMPRESSION - Cristina IONICI; Francico Cavas MARTINEZ (Fiabilitate şi Durabilitate)
Compression test at low temperature is 130-150 K range and the conditions set out in the technical execution of the tests carried out at low temperatures. As observed with MS do not behave traction to mechanical stress as compact material. The pore structure of the MS presence influence the mechanical behavior of which have been found in the case of mechanical compression test at room temperature.